Citing Medicine: The NLM Style Guide for Authors, Editors, and Publishers (Ukrainian translation) - Patrias, K.; Wendling, D. (Морфологія / Morphologia / Morfologìâ, 2017)
Citing Medicine: The NLM Style Guide for Authors, Editors, and Publishers (Ukrainian translation)